Reducing the Viscosity of High Paraffin Oils by the use of Situational Tasks in Teaching a Foreign Language in Non-Philological Universities - Asranov Sodik Aminzhonovich; Abduganieva Shakhlo Muminovna (International Journal on Orange Technologies, 2021)
This article discusses the issues related to the use of situational tasks in teaching a foreign language in non-philological universities. The experience of working in a national audience has shown that for the successful teaching of foreign languages, the communicative orientation of training should be given special attention